Changes in the thyroid gland in the long period after a new coronavirus infection - Choriyev, Saidmuhammad; Gadoeva, Zuhro; Mardonova, Fotima; Jurakulov, Farobiy; Hafizov, Shohruh; Daminov, Abdurasul Takhirovich (Science and Education, 2024)
Three years of the pandemic of the new coronavirus infection SARS-Cov-2 (SC-2) have raised a number of questions for doctors of various specialties regarding the mechanisms of action of this infection on the human body. The main target of coronavirus, undoubtedly, is the vascular system, but in such patients, doctors also identify many complications from other systems, including the endocrine system [1-3].